2008
DOI: 10.1111/j.1567-1364.2008.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of  the glycoside hydrolase activity of aBrettanomycesstrain on glycosides from sour cherry (Prunus cerasusL.) used in the production of special fruit beers

Abstract: The glycoside hydrolase activity of Saccharomyces cerevisiae and Brettanomyces custersii was examined on sour cherry (Prunus cerasus L.) glycosides with bound volatile compounds. Refermentations by the beta-glucosidase-negative S. cerevisiae strains LD25 and LD40 of sour cherry juice-supplemented beer demonstrated only a moderate increase of volatiles. In contrast, the beta-glucosidase-positive B. custersii strain LD72 showed a more pronounced activity towards glycosides with aliphatic alcohols, aromatic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 54 publications
(115 reference statements)
0
39
0
7
Order By: Relevance
“…Considering that benzaldehyde, a potential precursor of benzyl alcohol, did not vary among the wines, an alternative precursor of this aromatic alcohol could be its glycoside [20,21]. Enzymatic assay showed that T. delbrueckii yielded higher b-glucosidase activity than S. cerevisiae (0.90 ± 0.02 and 0.43 ± 0.01 mM/min/g dry weight, respectively, p \ 0.001) and it may explain the different benzyl alcohol concentration among wines.…”
Section: Aroma Analysismentioning
confidence: 99%
“…Considering that benzaldehyde, a potential precursor of benzyl alcohol, did not vary among the wines, an alternative precursor of this aromatic alcohol could be its glycoside [20,21]. Enzymatic assay showed that T. delbrueckii yielded higher b-glucosidase activity than S. cerevisiae (0.90 ± 0.02 and 0.43 ± 0.01 mM/min/g dry weight, respectively, p \ 0.001) and it may explain the different benzyl alcohol concentration among wines.…”
Section: Aroma Analysismentioning
confidence: 99%
“…This technique has been applied in the food industry for flavor modification, intensification, diversification, and/or differentiation ( Li and others ). For example, related research has been conducted in orange juice (Fan and others ), fruit beer (Daenen and others ), mango wine ( Li and others ), and other wines (Baffi and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested the use of β‐glucosidases for many other industrial applications, such as complete enzymatic degradation of cellulosic substrates and the production of aromatic compounds and biodegradable nonionic surfactants, apart from improving flavor (Daenen and others 2008; Maicas and Mateo 2005). Moreover, β‐glucosidases are also involved in transglycosylation reactions that synthesize oligosaccharides, alkyl glycosides, synthetic flavor precursors, glycosylated oligopeptides, and even precursors of glycolipids (Hiroyuki Kono and others 1999; Van Rantwijk and others 1999; Pal and others 2010).…”
Section: Introductionmentioning
confidence: 99%